GAYA BAHASA AMTSAL MUSHARRAHAH DALAM AL-QURAN (Suatu Kajian Tafsir Tematik) - Isramin Isramin (Fakultas Ushuluddin, Adab dan Dakwah, Universitas Islam Negeri (UIN) Datokarama Palu, Indonesia, 2016)
This paper introduces the reader to Amtsal Musharrahah in the Qur`an. Amtsal is the style of the Qur`an that is very typical in providing information and imagery. With this style, the language of the Qur`an has its own charm which shows that it is not a human language, but the word of God is eternal. Through thematic studies (maudhui interpretation) by searching several verses of the Qur'an containing amtsal, the authors conclude that the style of the Qur`an is beautiful, full of meaning and lessons. Through Musharrahah Amtsal style, Qur'an attracts people to pay attention to the messages contained in that paragraph. Not only that, through Amtsal, Qur'an describe something abstract into something that can be felt and seen directly. Finally, the style amtsal musharrahah not only touches one's mind, but more than it was touch and move unpleasant deepest, so that humans moved to accept the contents of the Qur`an.